INNATE IMMUNITY: MECHANISMS OF REALIZATION AND PATHOLOGICAL SYNDROMES. PART III - P.F. Litvitsky; T.G. Sinel'nikova ("Paediatrician" Publishers LLC, 2009)
The lecture analyzes a modern data on etiology, pathogenesis, and principles of treatment of primary and secondary insufficiency of innateimmune mechanisms, which are the result of disorders in two systems: phagocyte cells and complement. Key words: immunobiological response system surveillance, incomplete phagocytosis, phagocytal insufficiency, complement system insufficiency. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(3):54-65)